Cooperation between Convention Bureaus in Light of Empirical Research - Natalia Latuszek; Monika Dembińska (Barometr Regionalny, 2018)
The stakeholders’ cooperation in region (micro level) is recognized the basic source of cities’ competitive advantage in the meetings market. Though the cooperation also occurs between destinations (at the mezzo level), the existing studies rarely present it from this perspective. Cities on the meetings market are represented by specialized organizations, namely convention bureaus (CBs), whose function is to build and develop relations. The article aims to identify the significance of this function in the CBs operation, in face of progressive competitive processes. To achieve the research goal, an internet survey was conducted, addressed to the managers of the convention bureaus. The obtained data has been analyzed applying the Importance-Performance Analysis (IPA) method. The results of the study indicate a low priority for cooperation with other convention bureaus.